Smart anticorrosive coatings containing corrosion inhibitor-loaded halloysite nanotubes - Zahidah, K.A. (Elsevier, 2019)
This chapter introduces the smart epoxy coating on steel substrates, by the impregnation of active agents into halloysite nanotubes (HNTs) as nanocontainers for self-healing corrosion protection. Sodium diethyldithiocarbamate (SDEDTC) was used as a corrosion inhibitor. The loading efficiency of SDEDTC into HNTs was evaluated. HNTs (with or without inhibitors) were then introduced into the epoxy coating. An artificial scratch was made on the surface of each coated specimen. The electrochemical and immersion tests indicated the self-healing process of SDEDTC-loaded HNTs in the epoxy coating. Â© 2019 Elsevier Inc. All rights reserved.